2008
DOI: 10.1002/bdd.607
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of dihydroartemisinin in Artekin tablets for single and repeated dosing in Chinese healthy volunteers

Abstract: Aim. To study the pharmacokinetics of dihydroartemisinin (DHA) in Artekin (compound dihydroartemisinin) tablets in Chinese healthy volunteers. Methods. Eighteen healthy volunteers (9 males, 9 females) received Artekin tablets for oral administration. The plasma samples of DHA were analysed by liquid-liquid extraction and determined by HPLC/ESI/MS. Results. The plasma DHA concentration-time curves of single dose and repeated doses of DHA were fitted to a two-compartment open model. The mean pharmacokinetic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
(29 reference statements)
5
19
2
Order By: Relevance
“…The pharmacokinetic properties of dihydroartemisinin in healthy volunteers and nonpregnant patients with malaria have been well characterized with noncompartmental analysis, but no data on the population pharmacokinetics of dihydroartemisinin when administered as the fixed dihydroartemisinin-piperaquine combination are available (7,11,19,27,40,54). Results presented in this study for nonpregnant women with malaria are in agreement with previously published results for nonpregnant patients with uncomplicated malaria.…”
Section: Figsupporting
confidence: 89%
See 1 more Smart Citation
“…The pharmacokinetic properties of dihydroartemisinin in healthy volunteers and nonpregnant patients with malaria have been well characterized with noncompartmental analysis, but no data on the population pharmacokinetics of dihydroartemisinin when administered as the fixed dihydroartemisinin-piperaquine combination are available (7,11,19,27,40,54). Results presented in this study for nonpregnant women with malaria are in agreement with previously published results for nonpregnant patients with uncomplicated malaria.…”
Section: Figsupporting
confidence: 89%
“…Not enough data were collected in the absorption phase to support both an estimation of the drug transit rate and the absorption rate from the last transit compartment to the central compartment, and the two rate constants were therefore set to be identical. Dihydroartemisinin has previously been described by one-and two-compartment models, when modeled as individual concentration-time data in nonpregnant healthy volunteers and patients with malaria, which supports the structural model result in this study (19,26,38,39). Caution should be exerted when modeling artemisinin compounds since censoring of data (a high proportion of data below the limit of quantification at later time points) can lead to inappropriate structural models if model selection is based on statistical criterion alone (OFV) and not confirmed by simulation-based diagnostics (Fig.…”
Section: Figsupporting
confidence: 87%
“…The half-life of only 18 days in pregnant women and the low day 28 concentrations of PPQ suggest that at least monthly doses would be required when DHA-PPQ is considered for intermittent preventive treatment in pregnancy or chemoprophylaxis. Pharmacokinetic parameter estimates (clearance and apparent volume of distribution) for DHA were slightly higher than those previously reported in nonpregnant adult patients but lower than those reported in healthy volunteers (6,9,12,18,20). DHA exposure after the first dose was significantly lower in pregnant women; however, the differences were relatively small and may be explained by the high interindividual variability.…”
Section: Discussioncontrasting
confidence: 66%
“…However, previous detailed PK studies of oral and parenteral administration of ARS have demonstrated a clear malaria effect on the relative bioavailability thought to result from reduced first pass metabolism (40,41). The decreased absorption rate with increasing parasite density was unexpected and opposite to previous observations (39,(42)(43)(44)(45)(46)(47)(48). The underlying mechanism of this effect cannot be elucidated from data collected in this study.…”
Section: Population Pharmacokineticscontrasting
confidence: 85%